The Relation Between Life Style and Quality of Life on Hypertension Farmers in Panti District, Jember Regency - Pangestu, Adinda Widia; Kurdi, Fahruddin; Rasni, Hanny (Al-Hijrah Indonesia, 2024)
Farmers' unhealthy lifestyles may raise their risk of hypertension. The physical and mental effects of hypertension also impact farmers' quality of life. The study aimed to explain the connection between hypertensive farmers' lifestyles and quality of life in the Panti District of the Jember Regency. 204 farmers with hypertension were the subjects of this cross-sectional study, which utilized proportional random sampling. The WHOQOL-BREF Questionnaire and the Lifestyle Questionnaire are used in data collection to assess farmers' quality of life and lifestyle. The Spearman test with a value of 0.05 was used for data analysis. The Kolmogorov-Smirnov one-sample test revealed that hypertensive farmers in the Panti District had a significant lifestyle (p-value 0.00) based on the findings. Most hypertensive farmers in Jember Regency's Panti District lead healthy lifestyles. The Kolmogorov-Smirnov one sample test also shows that hypertension farmers in Panti District have a significantly better quality of life (p-value 0.00). Most hypertensive farmers in Panti District, Jember Regency (45.1%) live well. In hypertensive farmers in Panti District, Jember Regency, a relationship exists between lifestyle and quality of life (p-value 0.001). This study concludes that hypertensive farmers in Panti District, Jember Regency, have a better quality of life because of their lifestyle. Farmers can improve their health, reduce their risk of hypertension, and alleviate pain by changing their lifestyle. As a result, farmers' physical and mental well-being improves their quality of life.